PENUMBUHAN KESADARAN SEJARAH PESERTA DIDIK MELALUI METODE KARYAWISATA DALAM PEMBELAJARAN SEJARAH SITUS KERATON KADRIYAH - Mauludea, Hana (JURNAL PENDIDIKAN ILMU SOSIAL, 2015)
Site Kadriyah palace as local history studies should be intensified, in the teaching of history in schools. Method of learning utilization the local history field trip site Kadriyah palace in SMA Muhammadiyah 1 Pontianak was able to enhance the learners' enthusiasm for learning history. Conditions of a historical awareness of learners generally mixed. Some karatkter awareness of history found among others the emergence of attitudes prepared for the future, alert, creative, appreciate the past, the spirit of hard work and others. This study is expected to describe the historical consciousness and contribute to the teaching of local history in Pontianak and the surrounding area. Also expected to study the history of the palace site Kadriyah be intensified to be one source of learning history. Keywords: Consciousness the History, Methods of Field Trips, Local History, Sultan Kadriyah Site